A Computational Determination of the Origins of Diastereoselective Alkylations of a Cysteinesulfenate Anion. Issue 2 (16th November 2018) - Schwan, Adrian L.
Abstract : Sulfenic acid anions (RSO – ) represent an untapped functional group for the formation of sulfoxides and other organic compounds. Their stereoselective alkylation is an important component of this chemistry, but factors governing reaction outcomes are not fully understood. The current study uses Density Functional Theory methods to break down the influencing roles of substituents attached to 2‐aminoethanesulfenate. The lithium counterion can be coordinated to pendant ester or carbamate carbonyl groups, whereas the sulfenate oxygen readily participates in hydrogen bonding with proximal hydrogen atoms of the (protected) amino group. A Moc‐protected, ester substituted, 2‐aminoethanesulfenate adopts both lithium coordination and hydrogen bonding in the lowest energy form and demonstrates stereoselective methylation and benzylation consistent with experiments from the literature. Abstract : Density functional theory is employed to understand the preferred conformations adopted by a protected lithium cysteinesulfenate anion. Both sulfenate oxygen hydrogen bonding and carbonyl coordination of the substituents to the lithium counterion were found to be important stabilization modes. A preferred structure to account for diastereoselective methylation and benzylation at sulfur has been found.